The Teach-in on Global Warming Solutions and Vygotsky: Fostering ecological action and environmental citizenship - Lysack, Mishka (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractThe Teach-in on Global Warming Solutions is part of a larger socio-environmental movement concerned with combating climate change. Highlighting the history and elements of the teach-in as a model of learning, the article examines the teach-in movement, using a local event at the University of Calgary as an illustration. Conceptual resources from Vygotsky – the Zone of Proximal Development, and learning as social/relational transaction – are used to illuminate specific aspects of the teach-in. The article concludes by discussing the challenges and opportunities facing the global warming movement regarding public education.